Kinematic Characterization of the Pressure-Dependent Pcm Impregnation Process for Radiata Pine Wood Samples - Vasco-Calle, D (Springer Verlag, 2018)
This paper reports on the properties of Pinus radiata wood impregnated with an organic phase change material (O-PCM). The tests are aimed at characterizing the kinetics of impregnation (rates, flows, and fronts) and the thermophysical properties (thermal conductivity and specific heat). In particular, a paraffin type O-PCM (octadecane) is used to impregnate dry radiata pine wood in the tangential flow direction at four manometric pressures (0, 1, 2, and 3 bar) and constant temperature of 50 °C. The wood is sapwood from 12-year old P. radiata growing in the Bío-Bío region and dimensioned according to Chilean standard for treated wood sample extraction. The results show that it is viable to impregnate P. radiata wood with O-PCM to improve its thermophysical properties with the purpose of passive conditioning. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.